2021
DOI: 10.1088/1742-6596/1807/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Business Intelligence in Data and Information for Student Admission Process in Mulia University

Abstract: Mulia University is a private university that carries the slogan “Global Technopreneur Campus” with a total of 1631 students per August 2019. Mulia University has two campuses for learning support. The first one is Balikpapan Main Campus, and the other one is Samarinda Campus. The data to be used in this research is a prototype. Then, will be analyzed by Business Intelligent. Business intelligence is a series of processes to get information easily from large and complex data. In this research has been conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…No que se refere "sustainability" diversas publicações aplicam a ferramenta Power BI para analisar dados e obter insights relacionados a viabilidade financeira de gás biometano comprimido [Tonrangklang et al 2022], a modelos de economia circular em sistemas de gestão de resíduos para municípios de baixa renda [Vargas-Terranova et al 2022], ferramentas de sensoriamento ambiental para Indústria 4.0 [Krugh e Mears 2021], visualização de dados de veículos elétricos [Ayad et al 2020) e sistema de melhorias na qualidade e controle de fluxo de energia bidirecional de moinhos de vento [Valsala e Padmasuresh 2014]. Por fim, relacionado aos termos "visualization" e "dashboard" as publicações com aplicações do Power BI referem-se a análise de dados para insights sobre preferências de clientes de telecomunicação [Sharaf Addin et al 2022], monitoramento em tempo real de campanhas de imunização [Bello et al 2021], tomada de decisão de sistemas educacionais [Mutanov et al 2020], processos de admissão de estudantes em universidades [Mirwansyah et al 2021], previsões de demandas para setor de vendas [Gupta et al 2021], [Telaga et al 2019], sistemas de apoio a tomada de decisão para aumentar a disponibilidade de atendimentos médicos [Ovchinnikov et al 2021] e unidades de aluguel de veículos [Andriansyah e Nulhakim 2020], aumentar a adaptação de veículos elétricos [Ayad et al 2020], e até melhorias em processos de imigração [Roskladka et al 2020].…”
Section: Análise Sistemáticaunclassified
“…No que se refere "sustainability" diversas publicações aplicam a ferramenta Power BI para analisar dados e obter insights relacionados a viabilidade financeira de gás biometano comprimido [Tonrangklang et al 2022], a modelos de economia circular em sistemas de gestão de resíduos para municípios de baixa renda [Vargas-Terranova et al 2022], ferramentas de sensoriamento ambiental para Indústria 4.0 [Krugh e Mears 2021], visualização de dados de veículos elétricos [Ayad et al 2020) e sistema de melhorias na qualidade e controle de fluxo de energia bidirecional de moinhos de vento [Valsala e Padmasuresh 2014]. Por fim, relacionado aos termos "visualization" e "dashboard" as publicações com aplicações do Power BI referem-se a análise de dados para insights sobre preferências de clientes de telecomunicação [Sharaf Addin et al 2022], monitoramento em tempo real de campanhas de imunização [Bello et al 2021], tomada de decisão de sistemas educacionais [Mutanov et al 2020], processos de admissão de estudantes em universidades [Mirwansyah et al 2021], previsões de demandas para setor de vendas [Gupta et al 2021], [Telaga et al 2019], sistemas de apoio a tomada de decisão para aumentar a disponibilidade de atendimentos médicos [Ovchinnikov et al 2021] e unidades de aluguel de veículos [Andriansyah e Nulhakim 2020], aumentar a adaptação de veículos elétricos [Ayad et al 2020], e até melhorias em processos de imigração [Roskladka et al 2020].…”
Section: Análise Sistemáticaunclassified
“…When looking at the literature on business intelligence technology and higher education institutions, the fol-lowing topics come up: its applications (Hamad, 2021), improve performance in higher education (Abduldaem & Gravell, 2021), model to evaluate some national higher education (Khatibi et al, 2020;Ülker & Coşkun, 2021), analyzing educational data (Villegas-Ch et al, 2020), data and information for student admission process (Mirwansyah & Sari, 2021), governance framework in a university (Niño et al, 2020), quality management of higher education institutions (Pérez -Pérez, et al, 2018), performance measurement (Vallurupalli & Bose, 2018), course management systems (Van Dyk & Conradie, 2007), providing a framework and component dedicated for university's management (Muntean et al, 2011). Higher education and business intelligence studies have been conducted in a variety of disciplines, as may be shown.…”
Section: Business Intelligence (Bi) and Higher Educationmentioning
confidence: 99%